2013
DOI: 10.1246/cl.2013.292
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Adamantane Skeleton: Water Assembling around Amantadine and Halo-substituted Adamantanes

Abstract: We performed Monte Carlo simulations to reveal the water distributions around adamantane derivatives. Adamantane derivatives attract water molecules, and specific water distributions are observed around the skeleton. Perfluoroadamantane attracts water more than adamantane.Adamantane (C 10 H 16 ) is a highly symmetric tricyclic aliphatic hydrocarbon that is the simplest of the diamondoids, with a dipole moment of 0 D. Adamantane is known as a valuable building block for polymers for the enhancement of their th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
2
2
0
Order By: Relevance
“…For instance, the molecules corresponding to the top and bottom edges of that map (α ≈ 0.5π, β ≈ ±1π) are aligned parallel to the AD surface, with only small variations, and the dipole directions are oriented tangential to the AD surface. The frequent occurrence of such oriented molecules is consistent with previous Monte Carlo and MD simulations that used non polarizable force fields. , According to these studies, the water molecules in the first hydration shell are tangential to the skeleton surface of the AD. However, this is the single only orientational mode reported.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, the molecules corresponding to the top and bottom edges of that map (α ≈ 0.5π, β ≈ ±1π) are aligned parallel to the AD surface, with only small variations, and the dipole directions are oriented tangential to the AD surface. The frequent occurrence of such oriented molecules is consistent with previous Monte Carlo and MD simulations that used non polarizable force fields. , According to these studies, the water molecules in the first hydration shell are tangential to the skeleton surface of the AD. However, this is the single only orientational mode reported.…”
Section: Resultssupporting
confidence: 88%
“…This allowed us to shed new light on the electrostatic properties of the first hydration shell and its structure, which has been described as very unusual in experiments . We found a spectrum of water orientations, greatly expanding on what was known before in literature. , We showed that there are almost no interfacial C–H···O–H 2 bonds, in which we agree with experiments, except at very close distances to the interface, where they contribute to the stabilization of the water–water hydrogen bond network . However, we also showed that there is a substantial number of non-hydrogen bonded OH groups within the first hydration shell, which have also been observed around NDs and other hydrocarbons. , Generally, we found that for understanding hydrophobic hydration , it is of fundamental importance to know the effects of small surface perturbations on hydrophobic behavior.…”
Section: Discussionsupporting
confidence: 85%
“…The LennardJones parameters determined by Freindorf and Gao 15 were applied to the atoms of TMAO. The TIP3P water potential function 16 was employed for solvent molecules to compare the hydration pattern of TMAO with that of adamantane, 17 for which we had used TIP3P.…”
Section: ¹1mentioning
confidence: 99%
“…The number densities of O and H atoms of solvent water were calculated in the same way as in the previous work 17 (see Method S1). 12 The average dipole moment of solvent water at the position (x, y, z) was calculated, as follows:…”
Section: ¹3mentioning
confidence: 99%